On the presence of nanoscale heterogeneity in Al70Ni15Co15 metallic glass under pressure - Atila, Achraf; Kbirou, Meryem; Ouaskit, Said; Hasnaoui, Abdellatif (Journal of Non-Crystalline Solids, 2020)
We used molecular dynamics simulations to investigate the dependence of the atomic-scale structure on the temperature and pressure conditions of Al70Ni15Co15 metallic glass. The effect of pressure variations on the glass transition temperature was also studied, showing an increase with pressure. Moreover, radial distribution function, coordination number, and Voronoi tessellation analysis indicate that the applied pressure affects the local structure of glassy Al70Ni15Co15. We used a local symmetry parameter to access the glass-forming ability of the metallic glasses cooled under different pressures. The glasses cooled under high-pressures showed a significant fraction of embedded crystalline structure, which was found to be surrounded by a region of mixed-like clusters playing the role of an interface between the crystalline region and the glassy region. The correlation length, as calculated from the full width at half maximum of the first sharp diffraction peak, indicated an increase of the medium-range order with the increase of pressure. The evolution of the heterogeneity with pressure was highlighted by the existence of nanoscale crystals (1 to 4 nm in size)embedded in the amorphous zone. Finally, we discuss the results by referring to the atomic potential energy and stress.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Correlation length; Glass transition; Heterogeneity; Local atomic structure; Medium-range order